Flipped Classroom Integrates Problem-Based Learning: Enhancing Conceptual comprehension, Problem-Solving Abilities, and Self-Regulated Learning - Rahman Nul Hakim; Dhoriva Urwatul Wutsqo (Journal of Mathematics Science and Computer Education, 2026)
Indonesian students' mathematical conceptual comprehension, problem-solving skills, and self-regulated learning (SRL) remain persistent challenges. National assessment data reveals that students' mastery of combinatorics—the core topic of this study—is only 24.64%, with average mathematics scores in South Kalimantan at 36.69, far below the expected standard. These deficiencies highlight the need for innovative instructional approaches that simultaneously address cognitive and metacognitive competencies. This research investigates the efficacy of a flipped classroom combined with problem-based learning (FC-PBL) in improving students' conceptual comprehension, problem-solving abilities, and self-regulated learning within the context of mathematics. This quasi-experimental study engaged 12th-grade students who were separated into experimental (FC-PBL) and control (PBL only) groups. Instruction on combinatorics was provided to both groups, with pre-test and post-test administered to assess three learning outcomes. The findings indicated notable enhancements in conceptual comprehension and problem-solving capabilities in the FC-PBL group compared to the control group, as evidenced by a Hotelling's T² test and a Mahalanobis distance of D² = 1.72. However, SRL did not exhibit a statistically significant difference, reinforcing that student-centered approaches alone are insufficient to foster self-regulation without explicit scaffolding. These results imply that while FC-PBL presents a viable method for promoting mathematical comprehension and problem-solving, its effect on SRL necessitates further instructional support. The research offers empirical backing for the fusion of flipped and problem-based methodologies to tackle conceptual and procedural gaps in mathematics education.